2012
DOI: 10.1118/1.4762566
|View full text |Cite
|
Sign up to set email alerts
|

Penalization of aperture complexity in inversely planned volumetric modulated arc therapy

Abstract: The use of the edge penalty during optimization has the potential to markedly improve dose delivery accuracy for VMAT plans while still maintaining high quality optimized dose distributions. The penalty regularizes aperture shape and improves delivery efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
118
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(122 citation statements)
references
References 30 publications
1
118
0
3
Order By: Relevance
“…When compared to the plan using a MSW of 0.5 cm, the mean MU reductions in the plans using MSWs of 1.0 and 1.5 cm were 15.2% and 21.9%, respectively, while the total control points were decreased by 2.9% and 8.8%, respectively. Previous studies showed that decreasing the MUs for treatment delivery reduces the constraint factor of the leaves’ trajectories, complexity of intensity‐modulated radiation therapy plans, and treatment time 14, 15, 16, 17. Hence, as the MSW increases and VMAT plan complexity decreases, the therapeutic efficiency may improve as well.…”
Section: Discussionmentioning
confidence: 99%
“…When compared to the plan using a MSW of 0.5 cm, the mean MU reductions in the plans using MSWs of 1.0 and 1.5 cm were 15.2% and 21.9%, respectively, while the total control points were decreased by 2.9% and 8.8%, respectively. Previous studies showed that decreasing the MUs for treatment delivery reduces the constraint factor of the leaves’ trajectories, complexity of intensity‐modulated radiation therapy plans, and treatment time 14, 15, 16, 17. Hence, as the MSW increases and VMAT plan complexity decreases, the therapeutic efficiency may improve as well.…”
Section: Discussionmentioning
confidence: 99%
“…Also, a large decrease in plan modulation not only improves delivery efficiency, but also potentially decreases planning and quality assurance time or difficulty. [12][13][14][15] The patients undergoing hypofractionated treatment for tumors of the thorax and abdomen are more prone to have respiratory motion. These respiratory motions in the SBRT cases are manageable with the systems like Active Breathing Coordinator, respiratory gating, forced shallow breathing, etc., as per patient's comfort.…”
Section: Discussionmentioning
confidence: 99%
“…Young et al have discussed the use of edge penalty during optimization that reduces the required MUs up to 30% by avoiding the creation of complex apertures and increases accuracy of dose delivery with gamma passing rate from 79.5% to about 95.4%. 12 Hence the creation of such smaller segments can be controlled with sequencing parameters by the segmentation of theoretical fluence into deliverable MLC segments. The minimum segment width parameter in the segmentation process has a significant role in the creation of segments with different sizes and shapes.…”
Section: Introductionmentioning
confidence: 99%
“…With the transfer of these patients to the EDGE, a marked increase in plan modulation was observed, visualized both in the MLC‐leaf trajectory sequence in the Eclipse treatment planning system (TPS) as well as quantified by the number of monitor units (MU) and our in‐house VMAT complexity metric 3, 4. We also observed a sudden increase in plans failing patient‐specific quality assurance with the ArcCHECK (Sun Nuclear Corporation, Melbourne, FL, USA).…”
Section: Introductionmentioning
confidence: 99%